Effect of mango kernel flour addition on the phenolics profile, antioxidant activity and pasting properties of wheat flour - Irondi, E.A.; Awoyale, W.; Oboh, G.; Boligon, A.A. (Springer, 2017)
Improving the antioxidant and pasting properties of wheat flour could help enhance its health benefits and industrial uses. Hence, this study evaluated the effect of mango kernel flour addition on the phenolics profile, antioxidant activity and pasting properties of wheat flour. Wheat flour (WF) was mixed with mango kernel flour (MKF) at the ratios of 100:0; 90:10; and 80:20, to obtain 100%WF, WF-10%MKF and WF-20%MKF blends, respectively. The flavonoids and phenolic acids profile; free radicals (2,2-diphenylpicrylhydrazyl [DPPH]* and 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic [ABTS]*+) scavenging activities; amylose and amylopectin contents; and pasting properties of the 100%WF and the blends were determined. Flavonoids (rutin and quercetin) and phenolic acids (gallic, chlorogenic and caffeic acids) contents of the blends increased as the level of addition of MKF increased. The free radicals-scavenging activities of the blends also increased significantly (P < 0.05) as the level of addition of MKF increased. The DPPH* SC50 reduced from 7.04 ± 0.86 mg/mL (100%WF) to 4.51 ± 0.64 mg/mL (WF-20%MKF); while the ABTS*+ scavenging activity increased from 22.13 ± 1.24 mg/mL (100%WF) to 33.76 ± 1.92 mg/mL (WF-20%MKF). The amylose contents of the blends decreased significantly (P < 0.05), with a concomitant increase in their final and setback viscosities, as the level of addition of MKF increased. Hence, addition of MKF improved the antioxidant and pasting attributes of WF.